Predictors of clinical efficacy of 'Ablate and Pace' therapy in patients with permanent atrial fibrillation. Issue 4 (17th November 2011) - Brignole, M; Botto, G L; Mont, L; Oddone, D; Iacopino, S; De Marchi, G; Campoli, M; Sebastiani, V; Vincenti, A; Garcia Medina, D; Osca Asensi, J; Mocini, A; et al.
Abstract : Objective: To evaluate the 2-year clinical improvement after 'Ablate and Pace' therapy and to identify the variables able to influence the efficacy of this therapy in patients with permanent atrial fibrillation (AF). Design: Prospective multicentre observational study. Setting: Cardiology departments of 19 general hospitals in Italy, Spain and Greece. Patients: 171 patients with drug-refractory severely symptomatic permanent AF considered for AV junction ablation. Interventions: Patients underwent AV junction ablation, received a right ventricular (RV) pacing or echo-guided cardiac resynchronisation (CRT) pacing and were followed-up to 24 months. Main outcome measures: Non-responders to Ablate and Pace therapy were defined those patients who, during the follow-up period had clinical failure (defined as death or hospitalisation due to heart failure, or worsening heart failure) or showed no improvement in their clinical condition. Results: Responders were 63% of RV-paced patients and 83% of CRT-paced patients. Another 27% showed no clinical improvement (7%) or worsened (20%) (non-responders group). On multivariable Cox regression analysis, CRT mode and echo-optimised CRT were the only independent protective factors against non-response (HR=0.24, 95% CI 0.10–0.58, p=0.001 and HR=0.22, 95% CI 0.07–0.77, p=0.018 respectively). On comparing freedom from non-response, a trend in favour of echo-optimised CRT versus simultaneous biventricular pacing (p=0.077) was seen. Conclusions: In patients affected by severely symptomatic permanent AF, Ablate and Pace therapy yielded a clinical benefit in 63% of RV-paced patients and 83% of CRT-paced patients. CRT pacing and echo-optimised CRT were the only independent predictor of clinical benefit.